Validity of thorax-worn GPS heart rate data during continuous incremental and intermittent running - Fary, T.; Duthie, G.; Campbell, P.; Jennings, J.; Ballard, D.; Speranza, M.; Johnston, R. (Journal of Science and Medicine in Sport, 2025)
Objectives To determine the level of agreement between Catapult Vector S7 and Polar H10 for measuring heart rate (HR) during continuous incremental and intermittent running.